DNA Markers for Meat Quality of Pigs - Maksimov , Alexander; Fedyuk, Victor (KnE Life Sciences, 2021)
This paper presents the results of determining genotypes of 3-breed pig hybrids (Landrace x Yorkshire x Duroc) by marker genes MC4R (melanocortin receptor-4 gene), IGF2 (insulinoid growth factor-2), POU1F1 (pituitary transcription factor), H-FABP (protein gene binding fatty acids), GH (growth hormone gene), LEP (leptin gene) and their interrelation with meat productivity. Allele frequencies for the studied genes were determined (MC4R: А = 0.58, G = 0.42; IGF2: Q = 0.96, q = 0.04; POU1F1: Е = 0.66, F = 0.34; H-FABP: D = 0.38, d = 0.62; GH: А = 0.26, G = 0.74; LEP: С = 0.27, Т = 0.73). The study showed that 3-breed hybrids did not have the highest level of heterozygosity in most allelic genes. MC4R (AG = 48%), POU1F1 (EF = 68%) and H-FABP (Dd = 52%) genes had the greatest number of heterozygotes; IGF2 (QQ = 92%), GH (GG = 58%) and LEP (TT = 56%) genes had the greatest number of homozygotes. The data showed that the breeds used to obtain three-breed hybrids were selected for analogous (meat quality) traits and that they had a higher frequency of the desired Q (IGF2), G (GH) and T (LEP) gene alleles, which were lost from hybrids in the homozygous condition. We identified the most desirable genotypes for the studied genes (GGMC4R, AGMC4R, QQIGF2, EFPOU1F1, DDH-FABP, AAGH, CTLEP) which are recommended for pig selection as well as for selection of parent pairs for producing commercial hybrids with high meat productivity. Keywords: gene-dependent selection, slaughter and meat qualities of pigs, marker genes, MC4R, IGF2, POU1F1, H-FABP, GH, LEP